Outboard Engine Maintenance and Repair Training for Fishermen and Kelompok Sadar Wisata (PokDarWis) in Tlocor Sidoarjo - Gafur, Abdul; Haryono, Edi; Endro, R. Dimas; Alfanda, Benedcita Dian; Pramesti, Lely; Julianto, Eko; Santoso, Mardi; Kusminah, Imah Luluk; Antoko, Bambang; Ariwiyono, Nopem; Umbara, Albert Wida (Edumedia Solution, 2025)
Outboard Engine has been known and used as motor boat among of the residents of fisherman community in Tlocors village. Motor boats powered by outboard engine are not only used for fishing, but also used as marine tourism facilities. Considering the vital functional usage of outboard engine for Tlocor’s fisherman community and village community tourism groups (Pokdarwis), for maintaining economic livelihood, any interrupted items that happened during motor operation periods would be very significant impact on their daily life. Loss of income resulting from engine problem is the most of many potential cases occurred on the communities. Hence, it is necessary to provide assistances for both Tlocors Communities, the fishermen, and village community tourism groups. Assistances were also considered part of the public service obligation to communities provided by the Institution. Training on Outboard Engine Maintenance and Repair would become the scheme of the assistances. This tailor- made assistances would be targeted to both clusters. Better understanding and having a certain competency level on outboard engine maintenance and repair would have a significant value in order to empowering both communities, and become the main purpose of the assistance as well